2017
DOI: 10.1016/j.socscimed.2017.06.044
|View full text |Cite
|
Sign up to set email alerts
|

Pathways between childhood/adolescent adversity, adolescent socioeconomic status, and long-term cardiovascular disease risk in young adulthood

Abstract: Objective The current study investigated mediators between childhood/adolescent adversities (e.g., dating violence, maltreatment, homelessness, and parental death), low socioeconomic status (SES) during adolescence, and cardiovascular disease (CVD) risk in young adulthood. The purpose of these analyses was to understand whether SES during adolescence and childhood/adolescent adversities affect CVD risk through similar pathways, including maternal relationship quality, health behaviors, financial stress, medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
73
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(80 citation statements)
references
References 49 publications
5
73
0
2
Order By: Relevance
“…In the current study regarding socio-demographic characteristics of parents, only employment status in fathers and age in both parents played important roles, a result consistent with previous data, suggesting the in uential effect of family socioeconomic status (SES) de ned as parental employment and family income on children's general health and risk of CVD development in adulthood [34][35][36]. Accordingly, previous ndings in Iran showed that moderate and low familial economic status could increase the incidence of HTN in school-aged children [18].…”
Section: Discussionsupporting
confidence: 87%
“…In the current study regarding socio-demographic characteristics of parents, only employment status in fathers and age in both parents played important roles, a result consistent with previous data, suggesting the in uential effect of family socioeconomic status (SES) de ned as parental employment and family income on children's general health and risk of CVD development in adulthood [34][35][36]. Accordingly, previous ndings in Iran showed that moderate and low familial economic status could increase the incidence of HTN in school-aged children [18].…”
Section: Discussionsupporting
confidence: 87%
“…With regard to the role of financial resources, it has been well described a relationship with physical activity [24]. Data obtained from adolescents shows that the perception of living in low economical state will increase the general depressive symptoms.…”
Section: The Four Components In the Assessment Of Adolescents' Healthmentioning
confidence: 99%
“…127 Longitudinal designs are increasing in frequency, and a few longitudinal studies have assessed adversity in childhood and/or adolescence. 4,9,10,29,68,109,111,[128][129][130][131] As an example, the British National Child Development Study, a 50-year longitudinal study, assessed experiences of bullying when children were between 7 and 11 years of age. Bullying was associated with higher levels of C-reactive protein in midlife and, among women, with obesity in midlife.…”
Section: Clinical Statements and Guidelinesmentioning
confidence: 99%